An attempt to raise Thai students’ awareness of World Englishes in a General English Program - Krich Rajprasit; Roby Marlina (Indonesian JELT, 2019)
As witnessed over three decades in the field of Applied Linguistics, the emergence of world Englishes (hereafter WE), thanks to the global spread of English, has prompted various scholars to call for the need to critically revise the ways in which teachers teach English. Specifically, practitioners have been encouraged to raise their students’ awareness of WE. Examples of WE-informed curricula, modules, or lessons have been showcased by WE advocates from different parts of the world. However, most of these curricula, modules, and lessons are taught or delivered within TESOL teacher-education programs, leading some educators to question the relevance of WE to language learners. This paper showcases and evaluates critically how a WE-informed practitioner at one of the leading universities in Thailand attempts to inspire students enrolled in a General English program to develop respectful views of English language variation. Although the attempt has resulted in minor changes in students’ views, it certainly highlights that the teaching of world Englishes to English language learners is far from an idealistic attempt.